Pengembangan Lembar Kerja Peserta Didik Berbentuk Cerita Bergambar di Sekolah Dasar - Rahmawati; Firman; Bungawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of the research is to determine the need for developing LKPD in the form of picture stories, to find out the validity of LKPD in the form of picture stories, and to find out the practicality of LKPD in the form of picture stories. This type of research is R&D (Research and Development). The research was conducted at SDN 18 Maroangin. The data collection techniques in this research are observation, documentation, interviews and questionnaires. The results of the validity test of the LKPD in the form of illustrated stories showed that the assessment from learning material experts obtained a score with a percentage of 83.3% in the very valid category. Meanwhile, the assessment from media experts obtained a score with a percentage of 70% in the valid category and the assessment from language experts obtained a score with a percentage of 77.5% in the valid category. The results of the practicality test carried out on 28 class IV students and class teachers at SDN 18 Maroangin, obtained a percentage for the students' practicality score of 85.04% in the very practical category and for teachers the percentage obtained was 85% in the very practical category.